Genomic analysis of stayability in Nellore cattle - Teixeira, Daniela Barreto Amaral [UNESP]; Fernandes, Gerardo Alves [UNESP]; Dos Santos Silva, Danielly Beraldo [UNESP]; Costa, Raphael Bermal; Takada, Luciana [UNESP]; Gordo, Daniel Gustavo Mansan [UNESP]; Bresolin, Tiago [UNESP]; Carvalheiro, Roberto [UNESP]; Baldi, Fernando [UNESP]; De Albuquerque, Lucia Galvão [UNESP] (Public Library of Science (PLoS), 2017)
Stayability, which can be defined as the probability of a cow calving at a certain age when given the opportunity, is an important reproductive trait in beef cattle because it is directly related to herd profitability. The objective of this study was to estimate genetic parameters and to identify possible genomic regions associated with the phenotypic expression of stayability in Nellore cows. The variance components were estimated by Bayesian inference using a threshold animal model that included the systematic effects of contemporary group and sexual precocity and the random effects of animal and residual. The SNP effects were estimated by the single-step genomic BLUP method using information of 2,838 animals (2,020 females and 930 sires) genotyped with the Illumina High-Density BeadChip Array (San Diego, CA, USA). The variance explained by windows formed by 200 consecutive SNPs was used to identify genomic regions of largest effect on the expression of stayability. The heritability was 0.11 ± 0.01 when A matrix (pedigree) was used and 0.14 ± 0.01 when H matrix (relationship matrix that combines pedigree information and SNP data) was used. A total of 147 candidate genes for stayability were identified on chromosomes 1, 2, 5, 6, 9 and 20 and on the X chromosome. New candidate regions for stayability were detected, most of them related to reproductive, immunological and central nervous system functions.